The Impact of Podcasting on Mental Health Among Youth in Kampala Mainly at Uganda Christian University Main Campus and the Media Challenge Initiative Community - Michael Ainomugisha (Uganda Christian University, 2024)
This research examined the impact of podcasting on mental health among youth in Kampala, specifically at Uganda Christian University and the Media Challenge Initiative community. The study aimed to address the gap in understanding how mental health podcasts influence the well-being of young listeners. A qualitative research design was employed, utilising interviews and surveys to gather data from podcasters, mental health professionals, and youth participants. The findings revealed that podcasts serve as a valuable resource for mental health support, providing accessible information and fostering community engagement. Participants reported improved mental health awareness and coping strategies as a result of their podcast consumption. The study concluded that podcasting can play a significant role in addressing mental health issues among youth, suggesting that mental health professionals and content creators should collaborate to enhance the effectiveness of these digital platforms in promoting mental well-being.
Undergraduate Research
Keywords: Podcasting; Mental health; Media Challenge Initiative; Youth; Media